Autonomic Cardiovascular Assessment in Obstructive Sleep Apnea Using Beat-to-Beat Blood Pressure: A Pilot Study - Cremaschi, Renata Carvalho; Buitrago-Ricaute, Natalia; Novak, Peter; Coelho, Fernando Morgadinho Santos; Borges, Vanderci (Sleep Science, 2025)
To perform autonomic cardiovascular tests on patients with suspected OSA.In 2020, patients aged ≥18 years without difficult-to-control hypertension, cardiopathy, or pulmonary disease executed 6Hz deep breathing, 15-second Valsalva maneuver (40mmHg), and 5-minute active standing after the type 1 polysomnography at the Neurology (Federal University of São Paulo). The tests recorded blood pressure using beat-to-beat plethysmography, an electrocardiogram, and respiratory effort.Among the seventeen patients, ten had moderate OSA, and twelve were male. The mean age and disease duration were 52 and 14 years. Hypertension and obesity were frequent. They had mild autonomic symptom burden, mainly adrenergic sympathetic overactivity, and at least one-third of them had cardiovagal abnormalities.A small sample of patients with untreated moderate-to-severe OSA had autonomic abnormalities in tests using beat-to-beat blood pressure. Sympathetic overdrive in long-term daytime was manifested as orthostatic hypertension. Emerging technologies contributed to diagnosing the OSA-related autonomic dysfunction beyond the polysomnographic approach.
Keywords: autonomic; obstructive sleep apnea; cardiovagal; orthostatic hypertension; sympathetic